Fostering of Halal Culinary Products Through Marketing Innovation for MSME Partners in Meruya Selatan Village: Pengembangan Produk Kuliner Halal Dengan Inovasi Pemasaran pada Mitra UMKM Kelurahan Meruya Selatan - Setiany, Erna; HİDAYAH, Nurul; Setiyawati, Hari; Listyaningsih, Fransiska; Feriyanto, Dafit; Ramadhan, Kurnia; Zamzami, Annisa Hakim; Rahayu, Muthia; Hafidz IH, Muhammad (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of halal culinary products has become a key strategy to enhance the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia, particularly in Meruya Selatan. This article aims to identify and analyze the application of marketing innovations in the development of halal culinary products by MSME partners. The research employs a qualitative approach through in-depth interviews, observations, and document analysis involving several culinary MSMEs in the area. The findings reveal that marketing innovations, such as digital media utilization, product rebranding, and community-based collaborations, significantly contribute to increasing sales and expanding market reach. Additionally, halal certification provides added value, fostering consumer trust. Recommendations include strengthening the capacity of MSME actors through continuous training, leveraging information technology, and developing both local and global marketing networks. These measures aim to empower MSMEs in Meruya Selatan to contribute more substantially to local economic growth and support the national halal industry.